LEGAL AND INSTITUTIONAL FRAMEWORK FOR SAFETY AND HEALTH AT WORK IN THE REPUBLIC OF NORTH MACEDONIA - Majhosev, Andon; Paraklieva, Vera (Journal of process management and new technologies, 2019)
The safety and health at work are the unbreakable part of the work process. The International labour organization determined the safety and health at work as the primary international labour standard, and the Labour Law, as legal discipline, considers the safety and health at work as one of the basic legal principles within the labour relations. This work will analyze the provisions of the most important state acts referring to the safety and health at work, especially the Constitution, the Labour Relations Law and the Law on safety and health at work. In addition, this work will also analyze the provisions of several collective contracts in order to determine whether and in what manner this matter has been regulated. This work will also comprise the institutional establishment of the safety and health at work in the country.